2020
DOI: 10.5005/jp-journals-10071-23657
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical Profile and Fetomaternal Outcome of Obstetric Patients Admitted to Intensive Care Unit: A Prospective Hospital-based Study

Abstract: A bstract Aims and objectives To study clinical profile of obstetric patients admitted to intensive care unit (ICU) and to analyze the relation of demographic factors such as age, parity, literacy level, socioeconomic status, acute physiology and chronic health evaluation II (APACHE II) score, and level of delay with fetomaternal outcome. Design It is a prospective cross-sectional observational study. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…However, it was observed that the general scores were not able to accurately predict the outcomes of pregnant women in the critical care due to the physiological changes in pregnancy which have a bearing on the variables of these models; another reason being that many critical conditions improved remarkably after delivery of the fetus and placenta, leading to over prediction of mortality by the general scores. 12 , 13 , 16 , 18 24 Thus, the need for customization of the scores for obstetric patients was perceived. This led to development of specific ObPMs.…”
Section: Ethodsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it was observed that the general scores were not able to accurately predict the outcomes of pregnant women in the critical care due to the physiological changes in pregnancy which have a bearing on the variables of these models; another reason being that many critical conditions improved remarkably after delivery of the fetus and placenta, leading to over prediction of mortality by the general scores. 12 , 13 , 16 , 18 24 Thus, the need for customization of the scores for obstetric patients was perceived. This led to development of specific ObPMs.…”
Section: Ethodsmentioning
confidence: 99%
“… 25 It has three components, namely physiological variables (12 in number), age points, and chronic health points. Multiple authors, except Miglani et al, have reported overestimation of maternal mortality in obstetric patients using the APACHE II scores, including a comprehensive global analysis by Ryan et al 12 , 13 , 16 , 18 23 , 24 This overprediction was especially prominent in patients getting admitted for direct obstetric causes. 16 However, modified APACHE II scores (customized for obstetric population) could accurately (SMR: 0.86) predict mortality rates when compared with APACHE II (SMR: 0.36) in a study conducted by Paternina-Caicedo et al 26 Higher scores have been consistently associated with increasing risks of nonsurvival, near miss, need for advanced organ system support, prolonged ICU-LOS, perinatal mortality, and delay in hospital admissions (level 2 delay).…”
Section: Ethodsmentioning
confidence: 99%
See 3 more Smart Citations